Nutrient composition of selected cultivars of safflower (Carthamus tinctorius L.) leaves during different crop growth stages: NUTRIENT COMPOSITION OF SAFFLOWER LEAVES AT DIFFERENT CROP GROWTH STAGES - E SUNEEL KUMAR; APARNA KUNA; P PADMAVATHI; CH V DURGA RANI; SUPTA SARKAR (Journal of Oilseeds Research, 2016)
The changes in nutrient composition offour cultivars ofsafflower (Carthamus tinctorius L.) leaves (Annigeri-1, Manjira, TSF-1 and NARI-6) were estimated at three different crop growth stages viz., 30th (rosette stage), 50th (elongation stage) and 70th day (flower initiation stage). The results indicate that the moisture content in leaves was higher during the earlier stages (30th day) as compared to 50th and 70th days in all the four cultivars. The carbohydrate content was higher during 30th day as compared to 50th and 70th days in Annigeri-1, TSF-1 and NARI-6 varieties. Protein content varied between 2.51 to 4.04g/100g during various stages of maturity, while fat content was found to increase from 30th day (2.46g/100g) to 70th day (9.51g/100g) in all four cultivars. The crude fiber content ranged from 8.77 to 9.58g/100g, while ash content of safflower leaves ranged between 13.68 to 17.36 per cent during various stages of maturity in the four cultivars. Energy values of safflower ranged between 58.82 to 111.44 kcal/100g. Results indicated that safflower leaves were found to be rich sources of both iron (3.42 to 5.33mg/100g) and calcium(240 to 333.33mg/100g) during various stages of maturity in all the four cultivars. The results show that consumption of safflower leaves would contribute to very good content of carbohydrates, proteins, fiber, iron and calcium during all the stages of maturity though the content varies during various crop growth stages.